Evaluation of the Effectiveness of a Talent Management Program Based on Project Assignments in Enhancing the Loyalty of Red and White Cooperative Board Members in the Village Subdistrict - Mustamin B; Ahmad Ahmad; Patawari Patawari (Brilliant International Journal Of Management And Tourism, 2025)
Talent management has become an increasingly important strategic issue for cooperative organizations operating at the village subdistrict level, where organizational sustainability relies heavily on the commitment and loyalty of board members. In the context of the Red and White Cooperative, board members not only function as decision makers but also as implementers of development programs closely tied to community interests. However, existing talent management approaches are largely designed for corporate or public sector settings and often fail to accommodate the governance characteristics of cooperatives. This study aims to evaluate the effectiveness of a talent management program based on project assignments in enhancing the loyalty of Red and White Cooperative board members at the village subdistrict level. The research adopts a quasi experimental approach using a pretest posttest design with a comparison group. Data were collected through structured loyalty questionnaires covering affective, normative, continuance, and behavioral dimensions, complemented by administrative records, participation logs, and project documentation. Descriptive and comparative analyses were applied to examine changes in loyalty levels before and after program implementation. The results indicate that board members participating in the project based talent management program experienced a notable increase in overall loyalty, particularly in affective and behavioral dimensions, compared to the comparison group, which showed relatively stable conditions. The findings suggest that project assignments, supported by mentoring and feedback mechanisms, foster psychological ownership, responsibility, and sustained engagement among board members.